Algorithm for structural identification DYNAMICS MODELS Multidimensional OBJECT - Блохін, Л.М.; Безкоровайний, Ю.М.; Юрченко, О.М. (Proceedings of National Aviation University (archive), 2006)
The new algorithm of dynamic model structural identification of the multivariable stabilized plant with observable and unobservable disturbances in the regular operating modes is offered in this paper. With the help of the offered algorithm it is possible to define the perturbed models of dynamics not only of the plant, but also the dynamics characteristics of observable and unobservable casual disturbances taking into account the absence of low correlation between themselves and control inputs with the unobservable perturbations.